The Metaverse: Exploring consumer's expectations, their attitudes, and it's meaning to the fashion industry - Breiter Dennis; Siegfried Patrick (Tekstilna industrija, 2022)
The following paper aims to find out consumers' expectations and attitudes towards the innovation "Metaverse". It will also be explored which role the Meta Group plays in mass adaption and how the company influences consumers' possible use and opinion on the project. These results are connected to the fashion industry, further exploring new types of products and a possible distribution channel. Therefore, this study is useful to developers of Metaverses and AR/VR products, the Meta Group, and fashion companies. The main results of this research are: Meta and the Metaverse are seen as critical, the required technology has not yet reached mainstream use, but interest is present. Digital fashion had participants divided, some not willing to spend any money and some already having spent over 100€, although the Metaverse's influence on future purchases is little. The Metaverse could serve as a new distribution channel for clothing products. To conduct this research Google Forms was used. The research is classified as survey-based. The biggest limitation is the nonexistence of the Metaverse as envisioned by Meta, making it hard for participants to answer some of the questions asked.